Thermal decomposition of mixed metal oxalates - Coetzee, Anita (Rhodes University, Faculty of Science, Department of Chemistry, 1993)
The mixed metal oxalates, FeCu(ox)₂.3H₂0, CoCu(ox)₂.3H₂0, and NiCu(ox)₂.3.5H₂0, [ox = C₂0₄] have been prepared by coprecipitation from solution. The thermal behaviour of these compounds in nitrogen and in oxygen has been examined using thermogravimetry (TG), thermomagnetometry (TM), differential scanning calorimetry (DSC) and evolved gas analysis (EGA), and results are compared with results obtained for Cuox and Mox.yH₂0. The thermal behaviour of the mixed oxalates, MCU(OX)₂.xH₂0, differed from that of the individual metal oxalates, Cuox, Coox.2H₂0, Niox.2H₂0 and Feox.2H₂0. All three mixed oxalates on heating in N₂, first dehydrate and then decompose in at least two overlapping endothermic stages. Both CO and CO₂ were evolved in proportions which varied with the surrounding atmosphere, and from compound to compound, and with extent of reaction of a given compound. The mixed oxalates, MCU(OX)₂.xH₂0, do not show the exothermic behaviour characteristic of Cuox, and reasons for this are discussed. Thermochemical calculations were done and the enthalpies of formation of the hydrates and dehydrated oxalates were determined. It was found that the enthalpy of mixing was very small or within experimental error. X-ray powder diffraction patterns for the individual and mixed oxalates were compared. The pattern for Cuox differs from the patterns obtained for the other oxalates, confirming suggestions that Cuox has a structure different to most other transition metal oxalates. The kinetics of dehydration and decomposition of the mixed oxalates were investigated, using isothermal and programmed temperature TG and DSC experiments. The yield and composition of evolved gases during isothermal decomposition were measured and compared with the enthalpy changes. X-ray photoelectron spectroscopy studies provided some information on the electron environment of the metal atoms in the various oxalates.
Keywords: Oxalates -- Research; Decomposition (Chemistry)